2005
DOI: 10.1038/sj.onc.1208728
|View full text |Cite
|
Sign up to set email alerts
|

The breast cell growth inhibitor, estrogen down regulated gene 1, modulates a novel functional interaction between estrogen receptor alpha and transcriptional elongation factor cyclin T1

Abstract: Estrogen receptor alpha (ERa) regulates transcription of specific genes and is believed to play a major role in breast tumorigenesis. We previously identified estrogen down regulated gene 1 (EDG1 (also known as HEXIM1)) using the C-terminus of ERa (E/F domain) as bait in yeast twohybrid screenings. Here we report on the role of EDG1 as a coregulator of ERa transcriptional activity. We observe an interaction between EDG1 and ERa. EDG1 inhibits the transcriptional activity of ERa and this is dependent upon the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 30 publications
6
107
0
1
Order By: Relevance
“…Our observation extends already established mechanisms of repression by Hexim1, where its BR binds transcriptional activators and blocks their activity (20)(21)(22). In addition, our data reveal that Hexim1 can inhibit transcriptional activators in trans, by decoying P-TEFb away from them, which presents a conceptually previously undescribed mechanism for the inhibition of transcription by Hexim1.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Our observation extends already established mechanisms of repression by Hexim1, where its BR binds transcriptional activators and blocks their activity (20)(21)(22). In addition, our data reveal that Hexim1 can inhibit transcriptional activators in trans, by decoying P-TEFb away from them, which presents a conceptually previously undescribed mechanism for the inhibition of transcription by Hexim1.…”
Section: Discussionsupporting
confidence: 60%
“…Because BR in Hexim1 is necessary for the inhibition of p65, ER␣, and glucocorticoid receptors, we were interested in whether the same is true for CIITA (20)(21)(22). Surprisingly, the mutant f:NLS.Hex1(181-359) protein lacking the BR still inhibited the activity of CIITA to the same extent as the mutant f:Hex1 (150-359) protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6G-J). Given that ERα interacts with the positive transcription elongation factor-b (P-TEFb) complex that promotes transcriptional elongation in part by relieving the negative elongation factor (NELF) complex and stimulating RNAPII pSer2 (Wittmann et al 2005;Peterlin and Price 2006), which in turn promotes elongation-associated histone modifications (Pirngruber et al 2009), we further performed ChIP assays for CDK9 and NELF-A and observed that Ctr9 knockdown decreased the occupancy of CDK9 and increased the occupancy of NELF-A at CXCL12, GREB1, and PGR genes (Supplemental Fig. S15A-C).…”
Section: Ctr9 Regulates Estrogen-stimulated Transcription By Controllmentioning
confidence: 99%